(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issue of forming moral and ethical immunity against various information attacks affecting the consciousness of young people and society in the modern information space and their negative consequences. In particular, the psychological importance of the family environment in this process, the educational role of parents, and the need to form a strong worldview and information culture in children through the creation of a healthy psychological environment are substantiated. The study highlights the main functions of family psychology, information security, the process of socialization of young people and the role of spiritual values ​​in their formation as individuals.